Geopolitical risk perceptions - Yevheniia Bondarenko; Vivien Lewis; Matthias Rottner; Yves Schüler (Deutsche Bundesbank, 2024)
Geopolitical risk cannot be measured in a universal way. We develop new geopolitical risk indicators relying on local newspaper coverage to account for different perceptions. Using Russia as a case study, we demonstrate that geopolitical risk shocks identified from local news sources have significant adverse effects on the Russian economy, whereas geopolitical risk shocks identified from English-language news sources do not. We control for restricted press freedom by analyzing state-controlled and independent media separately. Employing a novel Russian sanctions index, we illustrate that geopolitical risk shocks propagate beyond the sanctions channel. Still, sanctions worsen the inflationary impact of geopolitical risk shocks substantially.
Keywords: E32; E44; E71; F44; F51; G41; 330; geopolitical risk; risk perceptions; Russia; sanctions; shock transmission